Legal Protection for Children in Conflict with the Law Based on Restorative Justice in the Women and Children Service Unit (UPPA) of the Bali Regional Police - Murdana, I Gede; Ketut Wiratny, Ni; Darma Saputra, Komang Edy Darma Saputra (Asian Journal of Social and Humanities, 2025)
The Constitution of the Republic of Indonesia, in Article 18B(2) of the 1945 Constitution, mandates that "Every child has the right to survival, growth, and development, as well as the right to protection from violence and discrimination." Furthermore, Article 20 of Law No. 17 of 2016 on the Enactment of Government Regulation in Lieu of Law No. 1 of 2016 Amending the Second Amendment to Law No. 23 of 2002 on Child Protection into Law. For this reason, the Criminal Justice System for Children Act No. 11 of 2012 was enacted. The Women and Children's Service Unit (PPA) in Bali, formerly known as the Special Service Room (RPK), has a long history. In 2007, the RPK was transformed into the PPA Unit pursuant to Police Chief Regulation No. Pol: 10 of 2007. This change aimed to enhance the effectiveness of handling cases involving women and children, as well as ensuring the protection of their rights. Prior to becoming the PPA Unit, it was tasked with providing specialized services to women and children who were victims of crime or perpetrators of criminal acts.